Treatment of symptomatic uterine leiomyoma with letrozole - Gurates, Bilgin; Parmaksiz, Cem; Kilic, Gokhan; Celik, Husnu; Kumru, Selahattin; Simsek, Mehmet (Elsevier Sci Ltd, 2008)
Uterine leiomyomas are the most common benign tumours of the female genital tract, often necessitating hysterectomy. The most common symptoms are dysmenorrhoea, menorrhagia, infertility and abortion. Ovarian hormones seem to play an essential role in pathogenesis, and deprivation of ovarian oestrogen causes leiomyomas to shrink significantly. The purpose of this study was to evaluate the effects of the non-steroidal aromatase inhibitor letrozole on uterine leiomyomas and on bone metabolism. A prospective, open clinical trial was conducted in a university-based hospital. Sixteen premenopausal women with symptomatic uterine leiomyomas were treated with letrozole 5 mg/day orally for 3 months. The main outcome measures of uterine and uterine leiomyoma sizes, serum FSH, LH, oestradiol concentrations, ovarian volumes and myoma-related symptoms were noted at baselines and once a month during treatment. Lumbar spine bone mineral density and biochemical markers of bone metabolism were studied at the beginning and at the end of 3 months. Letrozole significantly decreased uterine leiomyoma sizes (P < 0.01) and promptly benefited women with heavy menstrual bleeding associated with leiomyomas without changing bone mineral density. Aromatase inhibitors may represent a new generation of medications for the treatment of leiomyoma and associated symptoms. Larger clinical trials are needed, however, to fully evaluate their safety and efficacy.
Keywords: aromatase inhibitor; bone density/metabolism; myoma; oestrogen; uterine leiomyomata